Method for preparing carbon-encapsulated nickel nanoparticles based on solvent effect one-step method and application of carbon-encapsulated nickel nanoparticles
The one-step method of solvent effect is used to prepare carbon-encapsulated nickel nanoparticles, which solves the problem of poor conductivity of carbonaceous electrocatalysts, achieves efficient carbon dioxide reduction performance, and improves the catalytic efficiency of the electrocatalytic electrode.
Patent Information
- Application Number
- CN202411840942.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-14
AI Technical Summary
The existing carbonaceous electrocatalysts have poor conductivity, resulting in poor carbon dioxide reduction performance, low current density and low yield.
Carbon-encapsulated nickel nanoparticles were prepared by a one-step method based on the solvent effect, and Ni2+ was anchored by the strong coordination effect of 2-methylimidazole, and Ni2+ was pyrolyzed to reduce Ni2+ to Ni, promoting amorphous carbon graphitization, and improving the conductivity and stability of the catalyst.
It significantly improves the conductivity and stability of the catalyst, enhances the electrochemical carbon dioxide reduction capacity, and improves the catalytic efficiency of the electrocatalytic electrode.
Smart Images

Figure CN119615261A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical reduction technology, and in particular to a method and application of preparing carbon-encapsulated nickel nanoparticles in one step based on solvent effect. Technical Background
[0002] Excessive carbon dioxide emissions exacerbate global warming, leading to melting glaciers and frequent extreme weather. The development of carbon dioxide resource utilization technology can effectively alleviate environmental problems and energy crises. As a renewable carbon resource, carbon dioxide can be catalytically converted into carbon-containing chemicals and fuels to achieve high-value utilization. However, due to the high thermodynamic stability of carbon dioxide molecules, the breaking of the C=O bond requires a large amount of energy input. Using renewable energy as electric drive, efficient electrocatalytic reduction of carbon dioxide (CO2RR) can be achieved. On the other hand, the rational design of catalyst structure is the key to achieving directional conversion of carbon dioxide and improving the efficiency of carbon dioxide conversion.
[0003] Carbonaceous materials are cheap and readily available, and their potential electrochemical activity, strong chemical adsorption, high chemical stability and other advantages have attracted widespread attention in the field of carbon dioxide reduction. However, carbonaceous materials have weak activation ability for CO2 molecules, and other atoms need to be introduced to improve the CO2 catalytic activity. Compared with other doping elements, nitrogen has the following advantages: easy doping and high electronic / ionic conductivity. In addition, pyridinic nitrogen is considered to be the active center of CO2, which can enhance the original CO2RR activity of carbonaceous materials. Introducing metal-organic frameworks as precursors to construct nitrogen-doped carbon catalysts is an effective nitrogen doping strategy due to their high carbon content and easy heteroatom doping.
[0004] Although carbonaceous materials have the potential for CO2RR, the low amount of nitrogen atoms doped hinders the improvement of CO2RR performance, showing low current density and resulting in poor yield. Highly conductive metal materials can improve the electrochemical performance of carbonaceous materials. Nickel can not only improve the electron transport capacity of the catalyst, but also catalyze the graphitization of amorphous carbon and realize the graphitization process. The use of metal organic frameworks (MOFs) to confine Ni growth effectively avoids the agglomeration problem of metal ions during the reduction process and achieves high CO2RR performance. It has not been seen that the use of 2-methylimidazole coordination to reduce metal nickel catalyzes graphitization to enhance the outer layer of graphite carbon and prepare carbon-encapsulated nickel nanoparticles. Using different polarities of solvents to control Ni 2+ The reaction rate of Ni-Z IF precursor was significantly reduced with 2-methylimidazole, and then carbon-encapsulated Ni nanoparticles were synthesized by low-temperature pyrolysis. Summary of the invention
[0005] Aiming at the problem of poor conductivity of existing carbonaceous electrocatalysts, a method and application of preparing carbon-encapsulated nickel nanoparticles in one step based on polar effect is provided. This method uses the strong coordination effect of 2-methylimidazole to anchor Ni 2+ , thermal reduction of Ni 2 + The Ni nanoparticles inside promote the graphitization of amorphous carbon, improve the conductivity and stability of the catalyst, and enhance the electrochemical CO2 reduction ability.
[0006] The present invention provides a method and application of preparing carbon-encapsulated nickel nanoparticles in a one-step method based on solvent effect. The preparation steps of the method are as follows:
[0007] S1. Preparation of NiZ IF precursor:
[0008] Weigh a certain mass of 2-methylimidazole and dissolve it in a certain volume of methanol solution, and mix it ultrasonically to form a 2-methylimidazole solution. Weigh a certain mass of NiSO4·6H2O and dissolve it in a certain volume of deionized water, and mix it ultrasonically. Slowly drop the 2-methylimidazole solution into the above NiSO4·6H2O aqueous solution, and let the solution stand to separate into layers. The upper layer is yellow-green, and the lower layer is an emerald green transparent liquid. Then, slowly mix the solution at a low stirring speed. After uniform mixing, increase the stirring speed and continue stirring;
[0009] The mixed solution is centrifuged in a centrifuge to obtain a bright yellow precipitate after washing, which is then dried in a vacuum drying oven;
[0010] S2. Preparation of carbon encapsulated nickel nanoparticles:
[0011] The dried NiZ IF precursor was ground into powder and pyrolyzed under nitrogen atmosphere to obtain carbon-encapsulated nickel electrocatalyst.
[0012] Optionally, in step S1, the mass of 2-methylimidazole is 2.6-4 g, and the volume of methanol is 20-50 mL.
[0013] Optionally, in step S1, the mass of Ni SO4·6H2O is 0.5-3.2 g, the mass ratio of NiSO4·6H2O to 2-methylimidazole is between 0.2-0.8, the volume of the aqueous solution is 10-25 mL, and the volume ratio of methanol to water is between 1-2.
[0014] Optionally, in step S1, during the mixing process, the 2-methylimidazole solution is added dropwise to the NiSO4·6H2O aqueous solution, and the flow rate is controlled at 10-15 mL / min.
[0015] Optionally, in step S1, the mixing stirring speed is 60-120 r / min, and the stirring time is 1-5 min; after the mixture is evenly mixed, the stirring speed is increased to 200-400 r / min, and the stirring time is 8-24 h.
[0016] Optionally, in step S2, the flow rate of nitrogen is 3-8 mL, the calcination reaction time is 2-6 h, the calcination temperature is 400-800° C., and the heating rate is 3-10° C. / min.
[0017] Beneficial effects: The present invention provides a method and application for preparing carbon-encapsulated nickel nanoparticles in one step based on solvent effect, and the method has the following advantages:
[0018] S1. Using the different polarities of methanol and water molecules, Ni can be controlled 2+ The coordination environment with 2-methylimidazole stabilizes Ni 2+ , thereby preventing Ni 2+ Agglomeration problem during thermal reduction;
[0019] S2. Carbon encapsulated catalysts are prepared using Ni-MOF precursors. The central Ni nanoparticles can catalyze the graphitization of amorphous carbon, reduce the graphitization temperature, and achieve a low-temperature graphitization process. The outer graphite and the inner Ni layer both increase the electron transfer rate, thereby improving the catalytic efficiency of the electrocatalytic electrode.
[0020] S3. The one-step preparation of carbon-encapsulated nickel nanoparticles based on solvent effect has the characteristics of low preparation cost, simple preparation method, and controllable operating conditions, which is conducive to industrial production and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 A flow chart of the preparation method provided for an example of the present invention;
[0022] Figure 2 A scanning electron micrograph of a method for preparing carbon-encapsulated nickel nanoparticles based on solvent effect in one step provided by an example of the present invention;
[0023] Figure 3 is the linear sweep voltammogram of the prepared carbon-encapsulated nickel nanoparticles;
[0024] Figure 4 Faraday efficiency diagram of the prepared carbon-encapsulated nickel nanoparticles. DETAILED DESCRIPTION
[0025] Example 1: A one-step method for preparing carbon-encapsulated nickel nanoparticles based on solvent effect and its application
[0026] Weigh 3.24g of 2-methylimidazole and dissolve it in 25mL of methanol solution, mix it ultrasonically, and form a 2-methylimidazole solution. Weigh 2.06g of NiSO4·6H2O and dissolve it in 25mL of deionized water, and mix it ultrasonically. Add the 2-methylimidazole solution dropwise to the above NiSO4·6H2O aqueous solution at a flow rate of 10mL / min. The solution is allowed to stand for stratification. The upper layer is yellow-green and the lower layer is an emerald green transparent liquid. Subsequently, the solution is slowly mixed at a stirring speed of 60r / min. After uniform mixing, stir continuously at a stirring speed of 200r / min, place the above mixture in a centrifuge for centrifugation, wash it, and obtain a bright yellow precipitate product, which is placed in a vacuum drying oven and dried at 80°C. The dried Ni-Z IF precursor is ground into powder, the flow rate of nitrogen is 20mL / min, the calcination time is 2h, the calcination temperature is 550°C, and the heating rate is 5°C / min.
[0027] Example 2: A one-step method for preparing carbon-encapsulated nickel nanoparticles based on solvent effect and its application
[0028] The difference between this embodiment and embodiment 1 is that the mass of NiSO4·6H2O is different. Weigh 3.24g of 2-methylimidazole and dissolve it in 25mL of methanol solution, mix it ultrasonically, and form a 2-methylimidazole solution. Weigh 1.3g of Ni SO4·6H2O and dissolve it in 25mL of deionized water, and mix it ultrasonically. The 2-methylimidazole solution is added dropwise to the above NiSO4·6H2O aqueous solution at a flow rate of 10mL / min. The solution is allowed to stand for stratification. The upper layer is yellow-green and the lower layer is an emerald green transparent liquid. Subsequently, the solution is slowly mixed at a stirring speed of 60r / min. After being evenly mixed, stir continuously at a stirring speed of 200r / min, place the above mixed solution in a centrifuge for centrifugation, and obtain a bright yellow precipitate product after washing. Place it in a vacuum drying oven and dry it at 80°C. Grind the dried NiZ IF precursor into powder, the flow rate of nitrogen is 5mL / min, the calcination reaction time is 2h, the calcination temperature is 550°C, and the heating rate is 5°C / min.
[0029] Example 3: A one-step method for preparing carbon-encapsulated nickel nanoparticles based on solvent effect and its application
[0030] The difference between this embodiment and embodiment 2 is that the calcination temperature of the Ni-ZIF precursor is different. Weigh 3.24g of 2-methylimidazole and dissolve it in 25mL of methanol solution, and mix it ultrasonically to form a 2-methylimidazole solution. Weigh 1.3g of NiSO4·6H2O and dissolve it in 25mL of deionized water, and mix it ultrasonically. The 2-methylimidazole solution is added dropwise to the above NiSO4·6H2O aqueous solution at a flow rate of 10mL / min. The solution is allowed to stand and separate into layers. The upper layer is yellow-green, and the lower layer is an emerald green transparent liquid. Subsequently, the solution is slowly mixed at a stirring speed of 60r / min. After being evenly mixed, continue stirring at a stirring speed of 200 r / min, place the mixed solution in a centrifuge for centrifugation, obtain a bright yellow precipitate product after washing, place it in a vacuum drying oven at 80°C, and grind the dried NiZ IF precursor into powder. The flow rate of nitrogen is 20 mL / min, the calcination reaction time is 2 h, the calcination temperature is 700°C, and the heating rate is 5°C / min.
[0031] Example 4: A one-step method for preparing carbon-encapsulated nickel nanoparticles based on solvent effect and its application
[0032] The difference between this embodiment and embodiment 3 is that the calcination time of the Ni-ZIF precursor is different. Weigh 3.24g of 2-methylimidazole and dissolve it in 25mL of methanol solution, and mix it ultrasonically to form a 2-methylimidazole solution. Weigh 1.3g of NiSO4·6H2O and dissolve it in 25mL of deionized water, and mix it ultrasonically. The 2-methylimidazole solution is added dropwise to the above NiSO4·6H2O aqueous solution at a flow rate of 10mL / min. The solution is allowed to stand for stratification, and the upper layer is yellow-green, and the lower layer is an emerald green transparent liquid. Subsequently, the solution is slowly mixed at a stirring speed of 60r / min. After being evenly mixed, continue stirring at a stirring speed of 200 r / min, place the mixed solution in a centrifuge for centrifugation, obtain a bright yellow precipitate product after washing, place it in a vacuum drying oven at 80°C, and grind the dried NiZ IF precursor into powder. The flow rate of nitrogen is 20 mL / min, the calcination reaction time is 4 h, the calcination temperature is 700°C, and the heating rate is 5°C / min.
[0033] Experimental Example 1
[0034] The electrocatalytic CO2 activity experiment of the carbon-encapsulated nickel nanoparticles in Examples 1-3:
[0035] (1) Electrode preparation: 2 mg of the carbon-encapsulated nickel nanoparticles in Example 2 and Example 3 were weighed, respectively, and ultrasonically mixed with 160 mL of anhydrous ethanol and 30 mL of naphthol for 10 min to make a slurry, which was drop-coated on the surface of the pretreated carbon paper as a working electrode;
[0036] (2) The electrolyte solution was a 0.1 mol / L potassium bicarbonate solution. Before the test, CO2 was passed into the electrolyte solution for 20 min.
[0037] (3) Before testing, let the working electrode be at 100mV s -1 The test was repeated for 20 cycles to ensure more accurate experimental data. Platinum sheet and reference electrode were Ag / AgCl as counter electrode and reference electrode respectively. Linear sweep voltammetry (LSV) was used to test all polarization curves of all samples at a scan rate of 5mV / s. The results are shown in Figure 2. Figure 3 shown.
[0038] Depend on Figure 3 It can be seen that the catalysts prepared in Examples 1-3 have different electrocatalytic activities, among which the electrocatalytic CO2 activity of the catalyst prepared in Example 3 is higher than that of the catalysts prepared in Examples 1 and 2. When the applied voltage is -2.3 V vs. RHE, the electrochemical activity can reach 56 mA cm -2 .
[0039] Experimental Example 2
[0040] The electrocatalytic CO2 performance experiment of the carbon-encapsulated nickel nanoparticles in Examples 1-4:
[0041] (1) Carbon paper pretreatment: 2 The carbon paper was ultrasonically washed with ethanol and deionized water, alternating for 3 times, each time for 20 min;
[0042] (2) Electrode preparation: 2 mg of the carbon-encapsulated nickel nanoparticles in Examples 1-4 were weighed to prepare working electrodes;
[0043] (3) The counter electrode is a platinum sheet, the reference electrode is Ag / AgCl, and the CO2 reduction test is carried out in a 0.1 mol / L potassium bicarbonate electrolyte solution. The test voltage is between -0.78 and -1.18 V vs. RHE. The test results are as follows: Figure 4 shown.
[0044] Depend on Figure 4 It can be seen that the electrodes prepared by carbon-encapsulated nickel nanoparticles prepared in Examples 1-4 have different CO2 electroreduction activities. Among them, the Faraday efficiency of CO2 conversion to CO in Examples 2-4 is more than 80% in the full voltage range. The Faraday efficiency of CO2 conversion to CO in Example 3 is the highest at a voltage of -0.88V vs. RHE, which can reach 98%.
[0045] The applicant declares that the above embodiments are used to illustrate the detailed operation and process flow of the present invention, but are not limited to the above detailed operation and process flow. Those skilled in the relevant technical field should understand that any equivalent structure or equivalent process transformation made by using the description of the present invention, or directly or indirectly applied in other related technical fields, falls within the protection scope and disclosure scope of the present invention.
Claims
1. A simple preparation method and application of carbon encapsulated nickel nanoparticles based on solvent effect in one step, mainly comprising the following steps: S1. Preparation of Ni-ZIF precursor: Weigh a certain mass of 2-methylimidazole and dissolve it in a certain volume of methanol solution, and mix it ultrasonically to form a 2-methylimidazole solution. Weigh a certain mass of NiSO4·6H2O and dissolve it in a certain volume of deionized water, and mix it ultrasonically. Slowly drop the 2-methylimidazole solution into the above NiSO4·6H2O aqueous solution, and let the solution stand to separate into layers. The upper layer is yellow-green, and the lower layer is an emerald green transparent liquid. Then, slowly mix the solution at a lower stirring speed. After uniform mixing, increase the stirring speed and continue stirring; The mixed solution is centrifuged in a centrifuge, and a bright yellow precipitate is obtained after washing, which is then dried in a vacuum drying oven; S2. Preparation of carbon encapsulated nickel nanoparticles: The dried Ni-ZIF precursor was ground into powder and pyrolyzed under nitrogen atmosphere to form carbon-encapsulated nickel electrocatalyst.
2. According to claim 1, a simple preparation method and application of carbon-encapsulated nickel nanoparticles prepared in one step based on solvent effect, characterized in that: In the step S1, the mass of 2-methylimidazole is 2.6-4 g, and the volume of methanol is 20-50 mL.
3. The simple preparation method and application of carbon encapsulated nickel nanoparticles based on solvent effect in one step according to claim 1, characterized in that: In the step S1, the mass of NiSO4·5H2O is 0.52-3.2 g, the mass ratio of NiSO4·6H2O to 2-methylimidazole is between 0.2-0.8, the volume of the aqueous solution is 10-25 mL, and the volume ratio of methanol to water is between 1-2.
4. The simple preparation method and application of carbon encapsulated nickel nanoparticles based on solvent effect in one step according to claim 1, characterized in that: In the step S1, the 2-methylimidazole solution is slowly added dropwise to the NiSO4·6H2O aqueous solution during the mixing process, and the flow rate of the dimethylimidazole is controlled at 10-15 mL / min.
5. The simple preparation method and application of carbon encapsulated nickel nanoparticles based on solvent effect in one step according to claim 1, characterized in that: In the step S1, the mixing stirring speed is 60-120 r / min, and the stirring time is 1-5 min; after the mixture is evenly mixed, the stirring speed is increased to 200-400 r / min, and the stirring time is 8-24 h.
6. The method and application of preparing carbon-encapsulated nickel nanoparticles in one step based on solvent effect according to claim 1, characterized in that: In the step S2, the calcination temperature is 400-800°C, the heating rate is 3-10°C / min, the flow rate of nitrogen is 3-8mL, and the calcination reaction time is 2-6h.
7. Carbon-encapsulated nickel nanoparticles prepared according to the preparation method of any one of claims 1 to 6, characterized in that: The carbon-encapsulated nickel nano-electrocatalyst can be used to prepare electrodes for use in the technical field of electrocatalytic carbon dioxide reduction.